EFEK KONSUMSI BIO-YOGHURT DARI LACTOBACILLUS RHAMNOSUS SKG34 TERHADAP LIPID PROFILE PADA MANUSIA - I Desak Putu Kartika Pratiwi; Komang Ayu Nocianitri; Wayan Redi Aryanta; Yan Ramona; I Dewa Made Sukrama; I Nengah Sujaya (ARCHIVE OF COMMUNITY HEALTH, 2013)
This research was carried out to elucidate the eff ect of consumption bio-yoghurt produced byLactobacillus rhamnosus SKG34 on plasma lipid profi les in human. The study was performed usingpre and post analysis. Eleven healthy volunteers aged between 30-48 yeras old were participatedin this study. Each volunteers consumed 100g of bio-yoghurt containing L.rhamnosus SKG34 for 21 days. Blood samples were taken before the start of experiment and after 21 days of comsumption. Total cholesterol was measured using CHOP-POD method, while triglyceride determinedusing glycerol method, LDL and HD determined using homogenous method. Results of thestudy revealed that consumption of the bio-yoghurt lower values of plasma lipid concentrationsin hypercholesterolemia subjects. Total cholesterol, triglyceride and LDL was reduced within4.91%, 13.84%, and 8.24%, respectively, when compare to its concentrations before treatment.However, the plasma lipid concentrations in normal subjects were almost stable during thetreatment periods. Consumption of bio-yoghurt for 21 days had no eff ect on HDL-cholesterollevel. These results indicate that consumption of bio-yoghurt containing L.rhamnosus SKG34specifi cally lowered the concentrations of serum total cholesterol, LDL, and triglyceride onhypercholesterolemia subjects.